PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TWO STAY TWO STRAY (TSTS) UNTUK MENINGKATKAN HASIL BELAJAR PKn SISWA KELAS V SDN 50 BABUSSALAM KECAMATANMANDAU (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : Problems in this study is the low learning outcomes of students in the fifth grade Civics (V) SD Negeri 50 Babussalam, this can be seen from the results of the fifth grade students learn Civics (V) SD Negeri 50 Babussalam, with an average value of 68 classes (with KKM 70). The purpose of this research is to improve learning outcomes Civics Elementary School fifth grade students Saber sub 50 Babussalam the Implementation of Cooperative Learning Model TSTS. This research is a classroom action research (PTK) with two cycles in the second half of 2014/2015. Based on the analysis of the data research after applying the cooperative learning model of TSTS type, the average percentage of the activity of teachers in the first cycle of increase of 66.66% to 87.46% in the second cycle. The average percentage of student activity Increased Also items, namely 56.25% in the first cycle Increased to 83.33% in the second cycle. Student learning outcomes in basic score with an average of grade 68 and in the first cycle has Increased with an average value of 71.25 with the percentage improvement class learning outcomes 4.77% and the percentage of students who completed 65%, and the second cycle Increased again with an average of 75.50 with the percentage improvement class learning outcomes 11:02% and the percentage of students who completed 80%. Reviews These results indicate that the implementation of cooperative learning models can improve learning outcomes TSTS Civics fifth grade students of SD Negeri 50 Babussalam.Key Words: Learning ModelTSTS, CivicsLearning Outcomes